Clinical implementation and commissioning of the MedAustron Particle Therapy Accelerator for non‐isocentric scanned proton beam treatments. Issue 2 (29th December 2019) - Grevillot, Loïc; Osorio Moreno, Jhonnatan; Letellier, Virgile; Dreindl, Ralf; Elia, Alessio; Fuchs, Hermann; Carlino, Antonio; Kragl, Gabriele; Palmans, Hugo; Vatnitsky, Stanislav; Stock, Markus
Abstract : Purpose: This paper describes the clinical implementation and medical commissioning of the MedAustron Particle Therapy Accelerator (MAPTA) for non‐isocentric scanned proton beam treatments. Methods: Medical physics involvement during technical commissioning work is presented. Acceptance testing procedures, including advanced measurement methods of intra‐spill beam variations, are defined. Beam monitor calibration using two independent methods based on a dose‐area product formalism is described. Emphasis is given to the medical commissioning work and the specificities related to non‐isocentric irradiation, since a key feature of MedAustron is the routine delivery of non‐isocentric scanned proton beam treatments. Results: Key commissioning results and beam stability trend lines for more than 2 yr of clinical operation have been provided. Intra‐spill beam range, size, and position variations were within specifications of 0.3 mm, 15%, and 0.5 mm, respectively. The agreement between two independent beam monitor calibration methods was better than 1.0%. Non‐isocentric treatment delivery allowed lateral penumbra reduction of up to about 30%. Daily QA measurements of the beam range, size, position, and dose were always within 1 mm, 10%, 1 mm, and 2% from the baseline data, respectively. Conclusions: Non‐isocentric treatments have been successfully implemented at MedAustron for routine scanned proton beam therapy using horizontal and vertical fixed beamlines. Up to now every patient was treated in non‐isocentric conditions. The presented methodology to implement a new Scanned Ion Beam Delivery (SIBD) system into clinical routine for proton therapy may serve as a guidance for other centers.